Risk Factors for Patients Severe and Critical with Covid-19 - Nematov, A. A. (PT. Antis International Publisher, 2024)
In the fight against infectious diseases, the formation of collective immunity among the population is the main tool in the fight against diseases and the prevention of deaths. At the same time, even after vaccination, the occurrence of diseases among the population remains one of the current problems. Aim: To identify and assess risk factors for those with severe and very sever COVID-19. Materials and methods: Statistical analysis of the primary medical data of 1862 patients treated at the Republican Special Hospital for Infectious Diseases Zangiota №2, a retrospective research method was used. Results: When analyzing the patients infected with COVID-19 disease by age and gender groups, it was found that among the age groups under 20 years of age, the prevalence of the disease is almost the same among both sexes, where men are 4.88±0.2%, women are showed that 4.81±0.2%. When analyzing the patients infected with COVID-19 disease by age and gender groups, it was found that the prevalence of infection among both sexes is almost the same among the age groups under 20 years, where men are 4.88±0.2%, women are 4.81 showed that it is ±0.2%. We can explain the fact that the lifestyle and activities of these age groups in our country are almost the same, that is, they study in schools, lyceums and colleges. Among patients aged 20-49, the percentage of men is high (34.4±0.45%), while the percentage of women is slightly lower (29±0.43%). Conclusion: Factors that cause severe and very severe degree of COVID-19 include the elderly population, male sex, regular smokers, low socio economic populations, and people with chronic diseases was found to be.